KEHUMASAN DIGITAL: (Transformasi dan Kontribusi Industri 4.0 pada Stratejik Kehumasan) - Meranti Dhanussie Hasbiran (Kementerian Kominfo - RI, 2018)
ABSTRACTPublic relation has a very strategic role for an organization both commercial and non-profit. From time to time, public relations activities always experience development and transformation along with the increasingly complex needs of the role of public relations itself. By entering the industry era 4.0 characterized by digitalization and mobilization, the PR industry is adapting to a number of strategies that prioritize efficiency, high mobilization and greater target achievement. This strategic of public relations reflects the pattern that arises from disruption of industry 4.0, so it is worthy to be studied from the perspective of technology and communication management industry.